Assessment of Potential Toxicity of Alizarin Through Resonance Light Scattering - Li, Cha-Cha; Li, Jun-Sheng; Huang, Guo-Xia; Li, Qi-Qian; Yan, Liu-Juan (Asian Journal of Chemistry, 2012)
Alizarin is a kind of natural pigment. In this paper, saturation value binding with DNA of alizarin can be calculated by the resonance scattering spectrum and then is compared with mitoxantrone, chrysophano and rhein. Alizarin's potential toxicity is far lower than mitoxantrone and is slightly lower than chrysophano and rhein. The saturation value binding with DNA of alizarin can be influenced by many factors through studying different factors that influence the saturation value, that means the potential toxicity of alizarin are influenced by many factors. The saturation value at alizarin-DNA-pH 7.46 is 0.20. The saturation value at alizarin-DNA-pH 7.46-valine, alizarin-DNA-pH 7.46-leucine, alizarin-DNA-pH 7.46-histidine, alizarin-DNA-pH 7.46-aspartate, alizarin-DNA-pH 7.46- tryptophan, alizarin-DNA-pH 7.46-sodium chloride, alizarin-DNA-pH 7.46-glucose, alizarin-DNA-pH 6.44 and alizarin-DNA-pH 8.21 are 0.20, 0.20, 0.19, 0.24, 0.30, 0.4, 0.17, 0.17 and 0.19 respectively. Their change rate of the saturation value binding with DNA with alizarin-DNA-pH 7.46 as a standard are 0, 0, -5 %, +20 %, +50 %, +50 %, +100 %, -15 %, -15 % and -5 %. The aim of this paper is to provide a theoretical basis in using alizarin.